Alessandro Mendini et Casabella (1970-1976) : écrire et représenter la crise de l’architecture - Léa Battais (Amnis)
The editorials of Alessandro Mendini, architect and director of Casabella from 1970 to 1976, are the support and the manifestation of an intellectual and social crisis affecting architecture in the years of the Italian radical avant-garde. Mendini's mode of intervention within the magazine is emblematic of the transformation of the discipline, via the shift towards performance, happening, photography and film. The journal then welcomes traces of these creative moments, which are Casabella's collateral activities, as well as the micro-publications that present them. The periodical then becomes, under the impulse of its director, the organ of communication of an unofficial architecture and design of the postmodern avant-garde.